![F(x)+G(x)=3x^2+2x-2.](https://tex.z-dn.net/?f=F%28x%29%2BG%28x%29%3D3x%5E2%2B2x-2.)
Solution:
Given data:
and ![G(x)=2x-3](https://tex.z-dn.net/?f=G%28x%29%3D2x-3)
To find F(x) + G(x):
Adding two functions which gives another function.
Substitute F(x) and G(x), we get
![F(x)+G(x)=(3x^2+1)+(2x-3)](https://tex.z-dn.net/?f=F%28x%29%2BG%28x%29%3D%283x%5E2%2B1%29%2B%282x-3%29)
![=3x^2+1+2x-3](https://tex.z-dn.net/?f=%3D3x%5E2%2B1%2B2x-3)
![=3x^2+2x-3+1](https://tex.z-dn.net/?f=%3D3x%5E2%2B2x-3%2B1)
![=3x^2+2x-2](https://tex.z-dn.net/?f=%3D3x%5E2%2B2x-2)
![F(x)+G(x)=3x^2+2x-2](https://tex.z-dn.net/?f=F%28x%29%2BG%28x%29%3D3x%5E2%2B2x-2)
Hence, ![F(x)+G(x)=3x^2+2x-2.](https://tex.z-dn.net/?f=F%28x%29%2BG%28x%29%3D3x%5E2%2B2x-2.)
4(pi)m^2 = 144(pi)
4m^2 = 144
m^2 = 36
m = 6cm
diameter = 2m
= 2(6)
= 12cm
Answer:
Step-by-step explanation:a
Just take any two points from the graph. For example (4, -2) , (0, -3) Slope = (y2-y1) / (x2-x1) = -2-(-3) / 4-0 = 1/4